Group based metacognitive therapy for alcohol use disorder: a pilot study - Kroener, Julia; Eickholt, Maja Lara; Sosic-Vasic, Zrinka (Frontiers in Psychiatry, 2024)
Alcohol use disorder (AUD) is a severe clinical disorder, which has been associated with 5.3% of death worldwide. Although several treatments have been developed to improve AUD symptomatology, treatment effects were moderate, with a certain amount of patients displaying symptom deterioration after treatment termination. Moreover, outpatient treatment placements become increasingly scarce, thus necessitating more efficient treatment options. Therefore, the aim of the present study was to investigate the efficacy, feasibility, and acceptability of a newly invented, short, group based metacognitive therapy (MCT) for patients diagnosed with AUD. Seven patients were treated with eight sessions of group based MCT using a single case series design with an A-B replication across patients. Patients were assessed one month and one week before treatment, as well as one week and three months after treatment termination.Patients improved significantly and with large effect sizes regarding dysfunctional metacognitive beliefs, desire thinking/craving and depressive symptoms up to three months after treatment termination. AUD symptomatology as well as positive and negative metacognitive beliefs improved at post-treatment, but improvements could not be maintained at follow-up. All included patients completed the treatment and were highly satisfied. The presented findings show preliminary evidence for the efficacy, feasibility, and acceptability of the implemented group based MCT treatment. Large scale randomized controlled trials (RCTs) are needed to confirm the effectiveness of the developed program for patients diagnosed with AUD.